Effects of High g Values on Growth and Chlorophyll Content in Hydrated and Dehydrated Wheat Seeds - Jagtap, Sagar Shankar; Vidyasagar, P. B. (BULETIN FISIKA; Vol 21 No 2 (2020): BULETIN FISIKA, 2020)
Higher g value stimuli (gravitational acceleration more than 1 g and referred as hyper gravity) caused by centrifugation have been shown to inhibit elongation growth of various plants. In the present study, effects of high g values were studied on wheat seeds with and without water medium at the time of exposure to high g values. Wheat seeds (variety: LOK-1) were washed with 0.5% fungicide and then 4-5 times with distilled water (D/W). Seeds were then soaked in D/W for 24 hrs. Two different experiments were performed. In initial experiment, soaked seeds were taken into the centrifuge tubes filled with 1 ml D/W. Seeds were exposed to hypergravity ranging from 500 g to 2500 g for 10 minutes. In another experiment, soaked seeds were taken into the centrifuge tubes without water or any other medium and then exposed to high g values. After exposure seeds were immediately sowed on 0.8% agar gel. Results obtained showed that exposure to high g values suppressed growth in wheat seedlings when seeds were exposed to high g values with water as a medium. Chlorophyll content also decreased with increase in g. However, no change in growth and chlorophyll content were observed when seeds were exposed without water medium up to g values as high as 2500. Thus, effects of high g value stimuli depend not only on how much centrifugal force is applied to the seeds but also depends upon how much force is experienced by the inner part of the seeds.  Present observation shows that effective centrifugal force experienced by the seeds is different when applied with and without medium.